Educational and social values in the story of Naqa Saleh - mohammed, Asst.Lec. Zahra Akram Abdel Amir mohammed (Sulaimani Journal for Humanities, 2026)
The story of Saleh's camel mentioned in the Holy Qur’an is a rich example of social and educational lessons that reflect the moral values that must prevail between individuals and societies, as it represents a human experience full of meanings, as it highlights the relationship of man with God and the social environment in which he lives and the extent of his response to the challenges that face him, This research aims to explore the social and educational values derived from the story and how it can contribute to building a balanced moral society based on justice, respect and responsibility. This story provides a rich model through which the social and educational values that enhance societal harmony can be understood. The story highlights the importance of choosing the correct way to communicate with others from various cultural and social perceptions, as it explains the importance of conserving water and not wasting and wasting it. This story was mentioned in a multiple fence of the Holy Qur’an, and it came in Surat Al -Aaraf, Hood, Al -Hajar, Al -Ra’a, and Al -Israa, Al -Isra and other fences, and the focus in the story was on the miracle that the Prophet Saleh (peace be upon him) brought to his people, Thamud, and it was said that this camel was created from a rock and was said from A plateau, it was an unusual camel, which was made a verse on the sincerity of his prophethood
Keywords: Naqa Saleh; educational and social values; Thamud tribe; believe in God